Decadal Sedimentation in China's Largest Freshwater Lake, Poyang Lake - Xuefei Mei; Juan Du; Zhijun Dai; Jinzhou Du; Jinjuan Gao; Jie Wang (Geochemistry, Geophysics, Geosystems, 2018)
Abstract Lakes, as key recorders of sedimentation regime variations, have undergone dramatic erosion/deposition worldwide in response to global warming and increasing anthropogenic interference. Poyang Lake, China's largest freshwater lake, has not escaped these variations. Herein, we show that the sedimentation in Poyang Lake has likely undergone a unique phase shift from sediment sink (annually storing 421 × 104 t) during 1960–1999 to sediment source (yearly losing 782 × 104 t) during 2000–2012, with respect to the Changjiang (Yangtze) River. In comparison with sedimentation during 1960–1999, Poyang Lake sedimentation during the period 2000–2012 is characterized by no deposition during the flood season and enhanced erosion during the dry season. Furthermore, Poyang Lake's largest delta, the Ganjiang Delta, prograded at a rate of 32.7 m/a from 1983 to 1996, which increased to 52.8 m/a from 1996 to 2005 but dropped significantly to 1.7 m/a from 2005 to 2015. A sediment core collected in the shallow‐water shoal of the central lake indicates a stable increase in sedimentation flux from 1960 to 2002, with a mean value of 0.27 g/(cm2·a), followed by a decline in sedimentation flux after 2002. Our findings show that the tributary sediment input from the lake catchment dominated the sedimentation of Poyang Lake prior to 2000, when it was significantly larger than the sediment output to the Changjiang River. However, thereafter, the contribution of tributary sediment to the output dropped by 50%, and the rest has been provided by the lake itself. Namely, channels along Poyang Lake's waterway became the additional source of the lake's sediment output in the 2000s.